The Impact of Physical Activity on Non-Motor Symptoms in Parkinson’s Disease: A Systematic Review - Cusso, Melanie E.; Donald, Kenneth J.; Khoo, Tien K. (Frontiers in Medicine, 2016)
Parkinson’s disease (PD) is a neurological disorder that is associated with both motor and non-motor symptoms. The management of PD is primarily via pharmaceutical treatment, however non-pharmaceutical interventions have become increasingly recognised in the management of motor and non-motor symptoms (NMS). In this review, the efficacy of physical activity, including physiotherapy and occupational therapy, as an intervention in NMS will be assessed. The papers were extracted between the 20th to 22th of June 2016 from Pubmed, Web of Science, Medline, Ovid, SportsDiscuss and Scopus using the MeSH search terms ‘Parkinson’s’, ‘Parkinson’ and ‘Parkinsonism’ in conjunction with ‘exercise’, ‘physical activity’, ‘physiotherapy’, ‘occupational therapy’, ‘physical therapy’, ‘rehabilitation’, ‘dance’ and ‘martial arts’. Twenty studies matched inclusion criteria of having ten or more participants with diagnosed idiopathic PD participating in the intervention as well as having to evaluate the effects of physical activity on NMS in PD as controlled, randomized intervention studies. The outcomes of interest were NMS, including depression, cognition, fatigue, apathy, anxiety and sleep. Risk of bias in the studies was evaluated using the Cochrane Collaboration’s tool for assessing risk of bias. Comparability of the various intervention methods however was challenging due to demographic variability and methodological differences. Nevertheless, physical activity can positively impact the global NMS burden including depression, apathy, fatigue, day time sleepiness, sleep and cognition, thus supporting its therapeutic potential in neurodegenerative conditions such as PD. It is recommended that further adequately powered studies are conducted to assess the therapeutic role of physical activity on both motor and non-motor aspects of PD. These studies should be optimally designed to assess non-motor elements of disease using instruments validated in PD.